Planck-Scale GR Quantum Models of the Universe: Vacuum as a Coalescence of Micro-Universes; Particles as Micro-Photon Spheres Calculation of: Alpha; Lambda - Fèvre, Raymond (European Journal of Applied Sciences, 2026)
This article is a new completed version of EJAS 11804 (Vol. 10, N°1, Feb 25, 2022). It presents in a synthetic way three articles published in JHEPGC ([1], [2]), EJAS [12] and develops some aspects. Two hypotheses are studied. In the first one, the vacuum is endowed with a quantum structure in which the vacuum particles are Friedmann-Planck micro-universes. For this, the article introduces a quantization of a closed Friedmann universe, then a quantization of the photon spheres filling this universe. This approach gives a numerical value consistent with cosmological measurements for the current dark energy density and the cosmological constant of our Universe. Next, the second hypothesis takes the content of a model published in Physics Essays in 2013 [3], assuming that elementary particles are Schwarzschild photon spheres; these could be derived from the Friedmann photon spheres composing the vacuum particles. It is further recalled that the model presents au nified structure of elementary particles and allows us to calculate the value of the elementary electric charge and the fine structure constant. The masses of some elementary particles are calculated in a complementary model. Finally, this article summarizes a model of closed cyclic universe described in reference [2].This universe begins as one alone Friedmann-Planck micro-universe, then multiplying to constitute our Universe. Further a Big-Rip suddenly transforms it into a Friedmann-Planck macro-universe on a much larger scale. This one is the beginning of a new Big-Bang with the same evolution as ours. This process can be assumed to explain the existence of the initial FP micro-universe: it would be the result of a Big-Rip at the end of the evolution of a much smaller scale universe.